Happiness in the Javanese context: Exploring the role of emotion regulation and resilience - Taufik Akbar Rizqi Yunanto (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
Javanese, with their unique values, behaviors, and habits, represent the largest population among the many ethnicities in Indonesia. They adhere to specific values to maintain happiness in their lives, namely narima (acceptance) and rila (compliance). These values have psychological significance as they encompass resilience and the ability to regulate emotions. Furthermore, from a psychological perspective, resilience and emotion regulation play crucial roles in shaping the happiness of the Javanese population. Therefore, this study explores the relationship between emotion regulation, resilience, and happiness among the Javanese population. 250 Javanese from East Java and the Special Region of Yogyakarta were involved. This study utilized the interdependent happiness, resilience, and emotion regulation scales. The findings showed a significant relationship between resilience, emotion regulation, and happiness among Javanese. Both independent variables accounted for 51.8% of the happiness experienced by the participants. Therefore, these findings shed light on the psychological processes and mechanisms underlying happiness among Javanese.